Signifikansi Masyarakat Kitab Bagi Dialog Antariman: Telaah Eksploratif atas Konsepsi Mohammed Arkoun - Baedhowi - (Program Studi Ilmu Agama Islam Program Magister, Universitas Islam Indonesia, 2004)
This paper tries to discuss Arkoun's thought regarding the genuine concept of Revelation. His concept begins to elaborate Revelation in the history of al-Qur'an and Muslim Tradition. From historical background of Ahl al-Kitab (People of the Book) has been founded the same task and tool in history of salvation (HP). Beginning from decisive issues of Ahl al-Kitab, Arkoun works out the concept of